THE INFLUENCE OF SALARY AND FACILITIES ON EMPLOYEE WORK SPIRIT AT PT. BAKRIE SUMATRA MEDAN BRANCH PLANTATIONS - Hadi Pandjaitan (CV. Radja Publika, 2022)
A study must have a purpose, while the general objective of this study is to find out whether salary and facilities both partially and simultaneously affect the morale of employees at PT. Bakrie Sumatera Plantations Medan Branch and how much influence they have. From the results of the research that has been discussed by processing and questionnaires and using several tests it can be concluded that partially, the salary variable (X1) has a significant influence on the morale of employees of PT. Bakrie Sumatera Plantations Medan Branch. This means that the hypothesis in this study is accepted, as evidenced by the t count > t table (33,997> 1,999). While the facility variable (X2) has no significant effect on the morale of PT. Bakrie Sumatera Plantations Medan Branch. This means that the hypothesis in this study was rejected, as evidenced by the value of t count <t table (0.340 <1.999). Simultaneously, the variable salary (X1) and facilities (X2) have a significant influence on the morale of employees at PT. Bakrie Sumatera Plantations Medan Branch. This means that the hypothesis in this study is accepted, as evidenced by the calculated F value > F table (583,968> 3.15). The salary variable (X1) and facilities (X2) are able to contribute to the employee morale variable by 95% while the remaining 5% is influenced by other variables not examined in this study.